Accelerated mass production of influenza virus seed stocks in HEK-293 suspension cell cultures by reverse genetics. Issue 26 (8th June 2017) - Milián, Ernest; Julien, Thomas; Biaggio, Rafael; Venereo-Sanchez, Alina; Montes, Johnny; Manceur, Aziza P.; Ansorge, Sven; Petiot, Emma; Rosa-Calatrava, Manuel; Kamen, Amine
Highlights: HEK-293 cell culture is an efficient production platform for influenza A virus. Bioreactor production of H1N1 by Reverse Genetics in two-steps is demonstrated. The Rescue of influenza strain is streamlined for viral seed production. The sequence of the Influenza A virus produced is preserved along the process. The scalable process enables accelerated response to influenza pandemic threat. Abstract: Despite major advances in developing capacities and alternative technologies to egg-based production of influenza vaccines, responsiveness to an influenza pandemic threat is limited by the time it takes to generate a Candidate Vaccine Virus (CVV) as reported by the 2015 WHO Informal Consultation report titled "Influenza Vaccine Response during the Start of a Pandemic". In previous work, we have shown that HEK-293 cell culture in suspension and serum free medium is an efficient production platform for cell culture manufacturing of influenza candidate vaccines. This report, took advantage of, recombinant DNA technology using Reverse Genetics of influenza strains, and advances in the large-scale transfection of suspension cultured HEK-293 cells. We demonstrate the efficient generation of H1N1 with the PR8 backbone reassortant under controlled bioreactor conditions in two sequential steps (transfection/rescue and infection/production). This approach could deliver a CVV for influenza vaccine manufacturing within two-weeks, starting from HA and NA pandemic sequences. Furthermore, the scalability of the transfection technology combined with the HEK-293 platform has been extensively demonstrated at >100 L scale for several biologics, including recombinant viruses. Thus, this innovative approach is better suited to rationally engineer and mass produce influenza CVV within significantly shorter timelines to enable an effective global response in pandemic situations.